Detection of a circulating anodic antigen (CAA) of the Philippine strain schistosoma japonicum with monoclonal antibodies specific for CAA of S. mansoni - Acosta, Luz P.
2 IgG1 mouse monoclonal antibodies (mcabs), 147-1B4-AA and 120-1B10-A, both reactive with the same repeating epitope of a major circulating schistosome antigen, the circulating anodic antigen (CAA) of S. mansoni were used for this study. These mcabs were used in a standard 2-site Immunoradiometric Assay (IRMA), Immunoenzymetric Assay (IEMA) and in a Reverse Passive Hemagglutination test (RPHA) for the detection of CAA of S. mansoni and S. japonicum in TCA-treated Adult Worm Antigen (AWA-TCA). The IRMA and IEMA are comparable in sensitivity in detecting CAA in S. mansoni and S. japonicum whereas the RPHA is less sensitive. These assays also confirmed the cross-reactivity of CAA. of S. japonicum and S. mansoni. The CAA in S. japonicum-infected rabbit and mouse sera can be detected using the IEMA. Results also revealed a significant statistical difference between CAA level and initial cercarial dose (LIGHT and HEAVY) during the course of infection in experimental rabbits. The IEMA was also used to detect S. japonicum CAA in 368 human serum samples. Based on the results of duplicate Kato-katz examination of these patients, the IEMA detected 83 of the egg positive patients, and in 42 of egg negative patients. Results also revealed an increasing trend in CAA titers in LIGHT (100 epg), MODERATE (100 400) and HEAVY ( 400) egg output categories.